2023
DOI: 10.1002/tpg2.20321
|View full text |Cite
|
Sign up to set email alerts
|

Genomic‐assisted breeding for climate‐smart coffee

Abstract: Coffee is a universal beverage that drives a multi‐industry market on a global basis. Today, the sustainability of coffee production is threatened by accelerated climate changes. In this work, we propose the implementation of genomic‐assisted breeding for climate‐smart coffee in Coffea canephora. This species is adapted to higher temperatures and is more resilient to biotic and abiotic stresses. After evaluating two populations, over multiple harvests, and under severe drought weather condition, we dissected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Specifically, the heritability estimates varied between (0.1–0.74) [ Alkimim et al. (2020) and Alemayehu, 2019 ], (0.30–0.55) [ Gokavi et al., 2023 and Weldemichael et al., 2017 ], (0.30–0.51) [ Chrigui et al., 2020 and Ferrão et al., 2023 ], and (0.09–0.61) Alkimim et al., 2021 and Ferrão et al., 2023 ] for the YL, NF, LM, and Cer, respectively. Although the Pearson correlation between YL and the disease resistance traits were not statistically significant, a significant and positive genetic correlation (0.52) was obtained between YL and NF.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the heritability estimates varied between (0.1–0.74) [ Alkimim et al. (2020) and Alemayehu, 2019 ], (0.30–0.55) [ Gokavi et al., 2023 and Weldemichael et al., 2017 ], (0.30–0.51) [ Chrigui et al., 2020 and Ferrão et al., 2023 ], and (0.09–0.61) Alkimim et al., 2021 and Ferrão et al., 2023 ] for the YL, NF, LM, and Cer, respectively. Although the Pearson correlation between YL and the disease resistance traits were not statistically significant, a significant and positive genetic correlation (0.52) was obtained between YL and NF.…”
Section: Discussionmentioning
confidence: 99%
“…The study identified key candidate genes like CaTIFY4b and FRIGIDA that hold potential for enhancing drought tolerance in chickpea. In another study, Ferrão et al (2023) integrated GWAS and diallel analyses to investigate the genetic basis of key agronomic traits evaluated under drought environments in coffee. Molecular markers with major effects associated with disease resistance and post-harvest traits were identified, while yield and plant architecture displayed a polygenic background.…”
Section: Drought Tolerancementioning
confidence: 99%
“…Genomics-assisted breeding, at present, is employed to genetically improve plant species like Coffea arabica [153], sorghum [154], Virginia-type peanuts [155], Triticum sp. [156][157][158], pulses (pea, cowpea, faba-bean and lentil) [152], Cajanus cajan [159,160], Cicer arietinum, Arachis hypogaea [160], Avena Sativa [161], O. sativa [162], and many others.…”
Section: Gblupmentioning
confidence: 99%